Tracking diet variety in childhood and its association with eating behaviours related to appetite: The generation XXI birth cohort - Vilela, S (2018)
Research on the influence of early eating habits on eating behaviours related to appetite using a prospective approach is scarce, especially in children. The aim of this study was to explore the relationship between changes in diet variety from 4 to 7 years of age and appetitive traits measured at 7 years of age. Participants are from the population-based birth cohort Generation XXI (2005–2006). The present analysis included 4537 children with complete data on a food frequency questionnaire (FFQ) at both ages, and on the Children's Eating Behaviour Questionnaire at 7y. A healthy diet variety index (HDVI) was calculated at both ages using data from the FFQ. To assess tracking of diet variety, tertiles of HDVI scores were calculated and then re-categorized as ‘maintain: low’, ‘maintain: high’, ‘increase’ and ‘decrease’. Although the HDVI score decreased from 4 to 7y (p < .001), it showed a high stability, a positive predictive value, and a fair agreement. Increasing diet variety, compared to maintaining a low variety, was inversely associated with the ‘Desire to Drink’ (β = −0.090, 95%CI: 0.174; −0.006) and ‘Satiety Responsiveness’ (β = −0.119, 95%CI: 0.184; −0.054) subdimensions and positively with ‘Enjoyment of Food’ (β = 0.098, 95%CI: 0.023; 0.172) and ‘Emotional Overeating’ (β = 0.073, 95%CI: 0.006; 0.139). Those classified as either increase or maintain a high diet variety, in comparison with maintaining a low variety, had lower scores of ‘Food Fussiness’. In conclusion, diet variety decreased from 4 to 7y with a fair tracking. Children with a higher diet variety were less fussy, had a lower desire to drink and a higher general interest in food.